Ajuste de modelos autorregresivos que asumen valores enteros a datos de hurto a bicicletas en la localidad de Engativá de la ciudad de Bogotá D.C. (2023)
This degree work is based on the study of time series specifically of autoregressive processes that assume integer values. Orozco, (2017) is taken as a reference, which shows in detail the construction of some of these processes. This work begins with the concern of seeing recent theory in time series topics, which leads to studying advanced theory and which suggests asking: Does a mixed autoregressive model that assumes integer values ​​with first-order Poisson innovations fit better than a autoregressive for first-order integer values, to the data of high-impact crimes, bicycle theft in the town of Engativá in the city of Bogotá D. C between the years 2010 to 2016?